The Origin of the Fracture Networks in the Mudstones of Gale Crater Mars; Their Implications Regarding the State of Stress and Fluid Pressure During Their Formation and the Depth to Which They Were Buried. Issue 12 (14th December 2022) - Cosgrove, John W.; Banham, Steven G.; Gupta, Sanjeev; Barnes, Robert
Abstract: The aim of this article is to establish what can be determined about conditions on Mars during the formation of the fractures and veins that characterize the mudstones which crops out in Gale crater, and to determine whether these rocks represent superficial, alluvial deposits which have remained close to the surface or whether they have been subjected to significant burial and compaction. Spectacular, close‐up images of the fracture and vein networks on horizontal bedding planes reveal their geometries in great detail and this facilitates fracture analysis, a technique that can be used to determine the order in which the various fractures were formed and the stress field operating during their formation. The veins and their textures give an indication of the mechanism of formation of the fractures and of the possible role of high fluid pressures. In addition, the geometry of the veins when viewed in a vertical section can be used to indicate the amount of compaction that the mudstones have experienced which can be used to estimate the minimum depth of burial that has occurred. Plain Language Summary: Fractures on Mars can form in several ways: by desiccation, tectonic processes, or by hydraulic fracturing of the rock. By analyzing the geometries of the fracture networks, it is possible to determine their origin. The Curiosity rover frequently observes fractures along it's traverse, particularly in the laminated lacustrine Murray formation mudstones. By analyzing images of fractures on the bedding planes and from vertical sections, it can be demonstrated that the fractures formed as a result of high fluid pressures, rather than desiccation at the surface, or tectonic events. This would indicate that the low‐permeability Murray formation mudstones were buried to a depth sufficient to cause over pressuring and fracturing of the rocks. This implies substantial exhumation occurred to return these rocks to the surface. Key Points: The 3D geometry of the fracture networks in the mudstones on Mars have been used to reveal their mode of origin and the timing of their formation The polygonal arrangement of extensional fractures is the result of them forming in an overburden stress regime and is not the result of pre‐burial desiccation The fractures are hydraulic fractures which formed in response to an increase in fluid pressure associated with the burial and compaction of low‐permeability mudstones